The person in contemporary contexts of right-wing populism: an uncomfortable study - Luiz Fernando Dias Duarte; Marco Julián Martínez-Moreno (Vibrant: Virtual Brazilian Anthropology)
Abstract This article arises from the authors’ common concerns for the intense dissemination of versions of right-wing populism in Brazil over the preceding decade. The challenge of contemporary anthropology in relation to ‘uncomfortable’ phenomena, such as right-wing populism and the construction of the person involved in it, was the methodological and ethical focus adopted for this work. To achieve this, the historical antecedents of the phenomenon are revisited, and an overview of classical and contemporary theories and hypotheses are discussed-which enables us to recognise a structured pattern of affects, values, representations and practices that are reactive to enlightened Western modernity. As part of the epistemological and ethical responsibility of anthropological research, this framework offers elements of understanding of the processes through which people are constructed with worldviews that differ from the ideal-typical modern model, centred on the notion of the individual and the universal values involved in the recognition and promotion of human rights.